THE PERCEPTION OF STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA ON READING ENGLISH JOURNAL ARTICLES - Winda Silviana (PBI 15 UMY 036, 2015)
*36 Reading English journal articles is important for students in university. By reading English journal articles, the students get the information about research methods and various types of research that have been done by the researchers in the past. This research is focused on studentsof English Education Department of Universitas Muhammadiyah Yogyakarta perception in reading English journal articlesand to find the obstacle that students’ face in reading English journal articles. There were two research question presented in this research: (1) What are the students of English Education Department of Universitas Muhammadiyah Yogyakarta perceptions on reading English journal articles? (2) What are the obstacles faced by the students of English Education Department of Universitas Muhammadiyah Yogyakarta in reading English journal articles. The researcher applied qualitative research design and used interview as the research instrument. The participants were students of English Education Department of Universitas Muhammadiyah Yogyakarta in batch 2012 who ever joined in Issues in Language Teaching and Learning class. The result of this research showed that reading English journal articles is important and it is good to be implemented at English Education department of Universitas Muhammadiyah Yogyakarta. The students also have opinion that reading English journal articles give some advantages such as students’ vocabulary mastery improves, the students’ grammar knowledge increased. Reading English journalarticles promote students’ writing English skill and also increase students’ motivation in reading English text. The students also share their vi experience when using some reading strategies like skimming, scanning, and note taking. The problems faced by the students English Education Department of Universitas Muhammadiyah Yogyakarta is unfamiliar vocabulariesand sentence structure. The implementation of reading English journal articles gives some perceptions and obstacles from students of English education Department of Universitas Muhammadiyah Yogyakarta. Reading English journal articles is good and important to be implemented in English Education Department of Univesitas Muhammadiyah Yogyakarta. By reading English journal articles, the students get benefit on vocabulary, grammar, writing English skill and motivation. Sentence structure and unfamiliar vocabularies become the problems that students face when the students read English journal articles